2018
DOI: 10.1177/0363546518782701
|View full text |Cite
|
Sign up to set email alerts
|

The Presence and Degree of Bone Marrow Edema Influence Midterm Clinical Outcomes After Microfracture for Osteochondral Lesions of the Talus

Abstract: Patients with subchondral BME at midterm follow-up after microfracture for OLTs had worse clinical outcomes than those without subchondral BME. In addition, the degree of subchondral BME at midterm follow-up was correlated with clinical outcomes. However, at short-term follow-up, there were no significant differences in clinical outcomes based on both the presence and degree of BME, and no correlation was found between clinical outcomes and the degree of BME. The current study suggests that BME at short-term f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 33 publications
2
32
2
Order By: Relevance
“…This study showed results comparable with the overall outcome of approximately 85% success reported in previous studies. 33,34 In a systematic review, Zengerink et al 38 found that treatment was reported to be successful in 329 (85%) of 386 patients. In another systematic review, Donnenwerth and Roukis 8 reported that good to excellent functional outcomes were noted in 80.2% of 299 ankles.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed results comparable with the overall outcome of approximately 85% success reported in previous studies. 33,34 In a systematic review, Zengerink et al 38 found that treatment was reported to be successful in 329 (85%) of 386 patients. In another systematic review, Donnenwerth and Roukis 8 reported that good to excellent functional outcomes were noted in 80.2% of 299 ankles.…”
Section: Discussionmentioning
confidence: 99%
“…24 The association between postoperative MRI findings and clinical outcomes remains unclear. 1,22,33 Therefore, this study focused solely on clinical results after BMS.…”
Section: Discussionmentioning
confidence: 99%
“…The depth of a subchondral cyst or the presence of bone marrow edema was determined via the evaluation of fat-suppressed T2-weighted sequences. 33 After BMS, weightbearing ankle radiographs were taken at 3 months postoperatively and annually thereafter. The final radiograph was analyzed using the Takakura ankle osteoarthritis classification: stage 1, sclerosis and osteophyte formation without joint space narrowing; stage 2, medial joint space narrowing; stage 3, obliteration of medial joint space with subchondral bone contact; and stage 4, obliteration of the whole joint.…”
Section: Methodsmentioning
confidence: 99%
“…However, concern persists about subchondral bone damage after microfracture that may lead to poorer long-term clinical outcomes. 36…”
Section: Discussionmentioning
confidence: 99%
“…However, concern persists about subchondral bone damage after microfracture that may lead to poorer long-term clinical outcomes. 36 The majority of our patients were treated with excision and transtalar drilling and microfracture (n = 13). Five were treated with isolated transtalar drilling, 2 with transmalleolar drilling with abrasion chondroplasty, 1 with curettage and abrasion, and 1 with isolated microfracture.…”
Section: Methods Of Treatmentmentioning
confidence: 99%